DAMPAK BANTUAN SOSIAL PENGUATAN LEMBAGA DISTRIBUSI PANGAN MASYARAKAT (P-LDPM) TERHADAP KINERJA GAPOKTAN DI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Rahmat Akrima; Zainal Abidin; Rio Tedi Prayitno (Lampung University, 2016)
This research aims to assess the impact of P-LDPM on Gapoktan performances and rice farmers incomes member of Gapoktan in Natar District South Lampung Regency. The sample of this research includes two Gapoktan’s chairman, and 26 rice farmers from Gapoktan Pendowo (P-LDPM recipient) and Gapoktan Mekar Sari (non P-LDPM recipient). The data collection was conducted from April to May 2015. Performance of Gapoktan was analyzed by quantitative descriptive analysis; income of rice farmers was analyzed by independent t-test of two samples. The result of this research showed that P-LDPM gave impact on Gapoktan performance. This could be seen from the recipient of P-LDPM Gapoktan performance that showed a good performance, in two performance indicators set by the Ministry of Agriculture in 2013. While, non recipients P-LDPM Gapoktan only showed good performance in one indicator. Income of the farmer was not impacted by P-LDPM yet, this could be seen from the results of independent t-test of two samples analysis that showed no significant difference in the average income per hectare between recipients and non-recipients of Gapoktan members.Key words: gapoktan performance, impact, rice farmer’s income, P-LDPM